Controlled Exfoliation of Layered Silicate Heterostructures into Bilayers and Their Conversion into Giant Janus Platelets - Stoeter, Matthias; Goedrich, Sebastian; Feicht, Patrick; Rosenfeldt, Sabine; Thurn, Herbert; Neubauer, Jens W.; Seuss, Maximilian; Lindner, Peter; Kalo, Hussein; Moeller, Michael; Fery, Andreas; Foerster, Stephan; et al. (Angewandte Chemie International Edition, 2016)
Ordered heterostructures of layered materials where interlayers with different reactivities strictly alternate in stacks offer predetermined slippage planes that provide a precise route for the preparation of bilayer materials. We use this route for the synthesis of a novel type of reinforced layered silicate bilayer that is 15 % stiffer than the corresponding monolayer. Furthermore, we will demonstrate that triggering cleavage of bilayers by osmotic swelling gives access to a generic toolbox for an asymmetrical modification of the two vis-à-vis standing basal planes of monolayers. Only two simple steps applying arbitrary commercial polycations are needed to obtain such Janus-type monolayers. The generic synthesis route will be applicable to many other layered compounds capable of osmotic swelling, rendering this approach interesting for a variety of materials and applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic force microscopy; hybrid materials; nanomaterials; silicate; thin layers